1984
DOI: 10.1159/000215060
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Primary Hemostasis and Platelet Function after Alcohol Ingestion in Man

Abstract: The effect of alcohol ingestion on primary hemostasis was investigated in fasting healthy humans. Primary hemostasis was measured with the template bleeding time and platelet aggregation assayed with the turbidometric method. Blood was collected to study coagulation and fibrinolysis. 1 h after ingestion of 2 ml/kg body weight of 40% alcohol the plasma alcohol concentration was 19.3 ± 1.6 mmol/l. At this time there was a significant prolongation of the bleeding time accompanied by an impairment of platelet resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
(30 reference statements)
4
26
1
Order By: Relevance
“…In addition, impaired platelet function, altered liver functions and deranged coagulation parameters add to the existing maladies. 7 Our findings are in tune with above studies. In our study all the 4 patients with poor outcome [2 deaths] were males.…”
Section: Discussion: Analysis Of Resultssupporting
confidence: 92%
“…In addition, impaired platelet function, altered liver functions and deranged coagulation parameters add to the existing maladies. 7 Our findings are in tune with above studies. In our study all the 4 patients with poor outcome [2 deaths] were males.…”
Section: Discussion: Analysis Of Resultssupporting
confidence: 92%
“…16 Crossover trials of alcohol administration have variously reported dose-dependent decreases 14,28 or no change 29 in TPA activity. Most 12,16,24 but not all 15 studies indicate that alcohol increases TPA antigen concentrations, consistent with lower TPA activity.…”
Section: Previous Studies Of Alcohol and Hemostatic Factorsmentioning
confidence: 99%
“…7,9,11 Previous studies of the relation between alcohol consumption and hemostatic function have also been limited by small sample size, restriction to men, failure to distinguish between beverage types, and measurement of few hemostatic parameters. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] We therefore studied the relation between alcohol consumption and hemostatic function in 3223 adults enrolled in the Framingham Offspring Study, a prospective study of cardiovascular disease among the children of the original Framingham Heart Study subjects. 31 We studied both women and men, examined a broad range of coagulatory and fibrinolytic parameters, and considered the effects of individual beverage type.…”
mentioning
confidence: 99%
“…However, these studies have in general been performed on components of blood, rather than on whole blood, and the effects reported are not in agreement. Several studies have found an alcohol induced impairment of the primary hemostasis, whereas the humoral coagulation factors and the fibrinolytic system were unaffected [7][8][9]. El-Sayed et al [10] corroborated these results on the humoral coagulation factors and the fibrinolysis, but others have found an acute impairment of the fibrinolytic system by increased ethanol levels [11,12].…”
Section: Introductionmentioning
confidence: 98%